“Genome-wide identification of bZIP gene family in Pearl millet and transcriptional profiling under abiotic stress, phytohormonal treatments; and functional characterization of PgbZIP9” - Jha, Deepak Kumar; Chanwala, Jeky; Barla, Preeti; Dey, Nrisingha (Frontiers in Plant Science, 2024)
Abiotic stresses are major constraint in crop production, and they are accountable for more than half of the total crop loss. Plants overcome these environmental stresses using coordinated activities of transcription factors and phytohormones. Pearl millet an important C4 cereal plant having high nutritional value and climate resilient features is grown in marginal lands of Africa and South-East Asia including India. Among several transcription factors, the basic leucine zipper (bZIP) is an important TF family associated with diverse biological functions in plants. In this study, we have identified 98 bZIP family members (PgbZIP) in pearl millet. Phylogenetic analysis divided these PgbZIP genes into twelve groups (A-I, S, U and X). Motif analysis has shown that all the PgbZIP proteins possess conserved bZIP domains and the exon-intron organization revealed conserved structural features among the identified genes. Cis-element analysis, RNA-seq data analysis, and real-time expression analysis of PgbZIP genes suggested the potential role of selected PgbZIP genes in growth/development and abiotic stress responses in pearl millet.Expression profiling of selected PgbZIPs under various phytohormones (ABA, SA and MeJA) treatment showed differential expression patterns of PgbZIP genes. Further, PgbZIP9, a homolog of AtABI5 was found to localize in the nucleus and modulate gene expression in pearl millet under stresses. Our present findings provide a better understanding of bZIP genes in pearl millet and lay a good foundation for the further functional characterization of multi-stress tolerant PgbZIP genes, which could become efficient tools for crop improvement.